1997
DOI: 10.1007/s002560050262
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblastic metastases from breast carcinoma with false-negative bone scan

Abstract: The authors report a case of metastatic breast carcinoma that on investigation was shown to have a negative bone scan in spite of multiple densely sclerotic metastases on radiography and CT and a positive bone biopsy. The literature is reviewed with regard to the subject of negative bone scans in this situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…5 However, falsenegative results have been documented even in osteoblastic metastases. 6,7 The study showed that bone scintigraphy was not sensitive to detect micrometastases (2.3%) or more extensive intertrabecular metastases (3.3%). In addition, osteoblastic metastases were detected in only 57.6%.…”
Section: Radiological Imagingmentioning
confidence: 98%
“…5 However, falsenegative results have been documented even in osteoblastic metastases. 6,7 The study showed that bone scintigraphy was not sensitive to detect micrometastases (2.3%) or more extensive intertrabecular metastases (3.3%). In addition, osteoblastic metastases were detected in only 57.6%.…”
Section: Radiological Imagingmentioning
confidence: 98%
“…Specifically, CaP skeletal metastases are most often radiographically characterized as osteoblastic (i.e., increased mineral density at the site of the lesion) as opposed to osteolytic. Other tumors, such as breast cancer, can form osteoblastic lesions; however, these occur less frequently [Munk et al, 1997; Yamashita et al, 2000]. In spite of the radiographic osteoblastic appearance it is clear from histological evidence that CaP metastases form a heterogeneous mixture of osteolytic and osteoblastic lesions although osteoblastic lesions are predominant [Urwin et al, 1985; Percival et al, 1987; Berruti et al, 1996; Vinholes et al, 1996; Roudier et al, 2000].…”
mentioning
confidence: 99%
“…Specifically, prostate carcinoma skeletal metastases are most often characterized as osteoblastic (i.e., increased mineral density at the site of the lesion) as opposed to osteolytic. Other tumors, such as breast cancer, can form osteoblastic lesions; however, these occur less frequently [67,68].…”
Section: Prostate Skeletal Metastases Are Mixed Osteoblastic and Osteolytic Lesionsmentioning
confidence: 99%